Modernism/postmodernism - Brooker, Peter (Longman, 1992)
The concepts of 'Modernism' and 'Postmodernism' constitute the single most dominant issue of twentieth-century literature and culture and are the cause of much debate. In this influential volume, Peter Brooker presents some of the key viewpoints from a variety of major critics and sets these additionally alongside challenging arguments from Third World, Black and Feminist perspectives. His excellent Introduction and detailed headnotes for each section and essay provide an indispensable guide to interpreting the many different opinions, and prove to be valuable contributions in their own right.